2020
DOI: 10.18632/aging.202202
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA attenuates atherosclerosis via inhibiting NLRP3 inflammasome activation

Abstract: Tanshinone IIA (Tan IIA) possesses potent anti-atherogenic function, however, the underlying pharmacological mechanism remains incompletely understood. Previous studies suggest that oxidized LDL (oxLDL)-induced NLRP3 (NOD-like receptor (NLR) family, pyrin domain-containing protein 3) inflammasome activation in macrophages plays a vital role in atherogenesis. Whether the anti-atherogenic effect of Tan IIA relies on the inhibition of the NLRP3 inflammasome has not been investigated before. In this study, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…This phenomenon may attribute to the different microenvironment in cells. For example, tanshinone IIA attenuates atherosclerosis by inhibiting NLRP3 inflammasome activation in macrophages (19), while the expression of IL-1β and IL18 was inhibited in HeLa cells after tanshinone II A treatment (11). Briefly, the present study provides evidence to support tanshinone IIA as a potent drug to treat NPC.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This phenomenon may attribute to the different microenvironment in cells. For example, tanshinone IIA attenuates atherosclerosis by inhibiting NLRP3 inflammasome activation in macrophages (19), while the expression of IL-1β and IL18 was inhibited in HeLa cells after tanshinone II A treatment (11). Briefly, the present study provides evidence to support tanshinone IIA as a potent drug to treat NPC.…”
Section: Discussionsupporting
confidence: 55%
“…Notably, tanshinone IIA exhibits the opposite effect on normal cells and tumor cells, which may attribute to the different microenvironment. For example, tanshinone IIA attenuates atherosclerosis by inhibiting NLR family pyrin domain containing 3 (NLRP3) inflammasome activation in macrophages (19), while the expression of IL-1β and IL18 was inhibited in Hela cells after tanshinone II A treatment (11). Briefly, tanshinone IIA enhanced pyroptosis in HK1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al reported that tanshinone IIA increased cholesterol efflux and reduced lipid accumulation in macrophages, leading to a reduction in the development of aortic atherosclerosis [80]. Wen et al reported that tanshinone IIA inhibited oxidized LDL-induced NLRP3 inflammasome activation in mouse macrophages and ameliorated atherogenesis [81]. These findings indicated that tanshinone IIA possessed the potential activities for anti-inflammation and antiatherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…Tanshinone ⅡA could decrease oxidized low-density lipoprotein (oxLDL)-induced expression of lectin-like oxidized LDL receptor-1 (LOX-1) and CD36 ( Wen et al, 2020 ). And salvianolic acid B inhibited macrophage uptake of modified LDL in a scavenger receptor CD36–dependent manner ( Bao et al, 2012 ).…”
Section: Targeting Lipid Metabolism With Bioactive Compounds From Tcms With Anti-obesity Effectsmentioning
confidence: 99%